Minimization of energy efficiency barriers in the context of optimization of management decisions in the process of sustainable development - Bilous, Liliia (Technology audit and production reserves, 2021)
The object of research is the socioeconomic model of the country in terms of energy efficiency factors in the process of economic development. The author has adapted the taxonomy of barriers and identified a new group of barriers inherent in the socioeconomic models of countries with economies in transition. Achieving the goals of sustainable development is possible by achieving overall energy efficiency, which is provided by the implemented innovative energy technologies. The ability of the studied subjects to perceive and promote innovative energy technologies is determined by the level of their economic development. When building the concept of energy efficient management, the studied subjects should take into account the exhaustion of primary resources against the background of growing needs. One of Harrington's logical functions was used to determine the level of economic development of the studied subjects. In the indicators of the particular desirability of Harrington's logical function, indicators from 0.37 to 0.8 are the potential for development, currently unrealized in the studied subjects, which is the path to sustainable development. According to certain levels of private preferences, economic agents are given recommendations on the economic feasibility of introducing innovative energy technologies. At the same time, the research process involved the identification and localization of energy efficiency barriers in the studied subjects, which expanded the analytical opportunities in terms of providing practical recommendations. Such recommendations, combined with the private preferences of the studied subjects, allowed to formulate a conceptual scheme to increase the efficiency of energy resources of economic development management. The author proposes measures: scaling of grant financing, decentralization of energy sources, introduction of knowledge, cooperation of communities and in the community, development of entrepreneurship and greening of the environment. Directions strengthen the motivation of management decisions in the context of the effective impact of energy factors on the dynamics of economic development in modern conditions and can be used in the development of current and strategic plans and programs.